Anticancer activity of limonene: A systematic review of target signaling pathways. (17th April 2021) - Araújo‐Filho, Heitor Gomes de; dos Santos, Jucilene F.; Carvalho, Mikaella T. B.; Picot, Laurent; Fruitier‐Arnaudin, Ingrid; Groult, Hugo; Quintans‐Júnior, Lucindo J.; Quintans, Jullyana S.S.
Abstract : Limonene (LIM) is a monoterpene, which is abundant in essential oils of Citrus fruits peels (Rutaceae). More recently, LIM, as a potential natural anticancer compound, has attracted major attention and exerted a chemopreventive activity, stimulating the detoxification of carcinogenic compounds and limiting tumor growth and angiogenesis in various cancer models. Twenty‐six (26) articles were selected based on previously established criteria. Anticancer activity of LIM was related to the inhibition of tumor initiation, growth, and angiogenesis and the induction of cancer cells apoptosis. LIM was able to increase Bax expression, release cytochrome c, and activate the caspase pathway. In addition, LIM increased the expression of p53 and decreased the activity of Ras/Raf/MEK/ERK and PI3K/Akt pathways. LIM also decreased the expression of VEGF and increased the activities of the Man‐6‐P / IGF2R and TGF‐βIIR receptors. These results highlight LIM as an abundant natural molecule with low toxicity and pleiotropic pharmacological activity in cancer cells, targeting various cell‐signaling pathways critically involved in the initiation, growth, and chemoresistance of cancer cells.